Drawing workbook for engineering drawing and design - Jensen, Cecil Howard (Glencoe/McGwaw-Hill, 1997)
Engineering graphics as a language -- Basic drafting skills -- Applied geometry -- Theory of shape description -- Auxiliary views and revolutions -- Basic dimensioning - Sections -- Threaded fasteners -- Miscellaneous types of fasteners -- Manufacturing materials -- Forming processes -- Detail and assembly drawings -- Pictorial drawings -- Geometric dimensioning and tolerancing -- Drawings for numerical control -- Welding drawings -- Design concepts -- Belts, chains and gears